Investigation of the effects of steam injection on performance and NO emissions of a diesel engine running with ethanol-diesel blend - Gonca, Guven (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The use of ethanol-diesel blends in diesel engines without any modifications negatively affects the engine performance and NOx emissions. However, steam injection method decreases NOx emissions and improves the engine performance. In this study, steam injection method is applied into a single cylinder, four-stroke, direct injection, naturally aspirated diesel engine fueled with ethanol-diesel blend in order improve the performance and NOx emissions by using two-zone combustion model for 15% ethanol addition and 20% steam ratios at full load condition. The results obtained are compared with conventional diesel engine (D), steam injected diesel engine (D + S20), diesel engine fueled with ethanol-diesel blend (E15) and steam injected diesel engine fueled with ethanol-diesel blend (E15 + S20) in terms of performance and NO emissions. The results showed that as NO emissions considerably decrease the performance significantly increases with steam injection method. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ethanol; Engine performance; Steam injection; NO emission; Two-zone combustion model; Diesel engine; EXHAUST-GAS RECIRCULATION; DUAL FUEL ENGINE; COMBUSTION CHARACTERISTICS; COMPRESSION-IGNITION; ALTERNATIVE FUELS; EMULSIFIED FUEL; FUMIGATION; PARAMETERS; SYSTEM; Thermodynamics; Energy & Fuels; Mechanics